The mental health of community correctional officers: supervising persons with serious mental illness. Issue 2 (2nd April 2020) - Powell, Nicholas; Gayman, Mathew D
ABSTRACT: Few studies have investigated factors that contribute to the mental health of probation and parole officers (PPOs). Addressing the needs of supervisees with serious mental illness (SMI) can create unique challenges for PPOs, which in turn may increase job-related stress and impact PPOs' mental health. Using statewide survey data from 795 PPOs, we examine whether the number of supervisees with SMI on an officer's caseload is associated with depressive symptoms reported by PPOs and whether this relationship is mediated by work stress. In addition, we examine the mediating effects of role conflict and overload in the relationship between the number of persons with SMI on an officer's caseload and work stress. Findings reveal that PPOs supervising more people with SMI report significantly higher levels of depressive symptoms and this relationship is mediated by work stress. Additionally, the association between the number of supervisees with SMI on an officer's caseload and work stress is completely explained away by role conflict and role overload. These findings highlight the mental health significance for parole and probation practitioners working with persons with SMI.